University orientation after the pandemic: a model student service competence - Ibáñez Martínez, Raquel; Alonso Larza, Lucía (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper focuses on the university context after the pandemic. Universities have been forced to modify their daily routine, implementing a series of measures in order to comply with the established security protocols, without neglecting the teaching-learning process and the attention to their students. They have had to adapt to a new reality, not without difficulties. The key role of guidance services in universities is highlighted and a model of competency-based guidance is proposed through which to respond to the new needs generated after the pandemic.